Implementation of the Outing Class Learning Model to Improve Memorization Skills at the Khairaatun Hisaan Carawali Girls' Islamic Boarding School, Sidrap Regency - Nurul Ainun. SK; M. Nasir; Muhammad Fadli (Universitas Muhammadiyah Palu, 2026)
The process of memorizing the Qur'an in Islamic boarding schools often faces the challenge of boredom and decreased concentration of students due to monotonous learning routines indoors. This static learning environment reduces motivation and memorization effectiveness, although the outdoors has great potential to improve concentration. The lack of variety of learning methods and the maximum use of the outside environment is the main problem. This study aims to analyze the implementation of the Outing Class learning method at the Putri Khairaatun Hisaan Carawali Islamic Boarding School, Sidrap Regency. The main focus is to evaluate how this method improves students' focus, concentration, and memorization ability of the Qur'an. This study uses a qualitative approach with a case study method. Data was collected through participatory observation, in-depth interviews with Islamic boarding school leaders, ustadzah, and students, and document studies. Data analysis involves reducing, presenting, and drawing conclusions. The application of the Outing Class method showed a significant positive impact on the process of memorizing the Qur'an. Students feel more motivated, comfortable, and focused when memorizing in an outdoor environment, which reduces boredom and improves memory and confidence. Even though there are minor external disturbances, students can still concentrate. This method also increases intimate interaction between teachers and students, and encourages active learning. The Outing Class succeeded in integrating various learning theories, improving quantitative memorization results, and strengthening the cognitive, affective, and psychomotor aspects of students. Outing Class is an effective strategic innovation in learning tahfiz Al-Qur'an, creating a fun learning experience, increasing motivation, focus, and memorization effectiveness, and forming a positive character of students. This method is recommended to be integrated into the pesantren curriculum.